The spin doctor behaviour matrix at the political communication process (Comunicação & Inovação, 2015)
In the mid-eighties was born a new name for theactivity of the political press relations: the spindoctoring. Much has been said of spin doctorsand their way of acting, but we do not always realizethe extent to which their actions differ fromthe normative model of the traditional media relations.Thus, this article propose to explain 36techniques, actions and behaviours that resultin a behaviour matrix of these sophisticated informationsources operating in the service ofgovernments, political parties and even privatecompanies.
Keywords: Spin doctoring. Media relations. Political communication.